PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME PADA MATERI LINGKARAN DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMPN 2 BAYANG - Sisriwati, Yefi Yuni (Pendidikan Matematika, 2014)
This research was motivated because of the students difficulties in constructing theconcepts, and lack of the learning sources that facilitate the students to learnindependently is still lacking, and students difficult was to understand the material on avast circle, circumference, area segment, central angle and the angle circumference. Toovercome these problems, the constructivis based module was developed for circlematerial. This study aimed to develop a valid and practicalities module basedconstructivism in SMPN 2 Bayang. This type of research was a development research.This study used model of 4-D which consisted of 4 phases: definition, design,development and disseminate phases. This study was only done in 3 phases. Thedevelopment phase was done to see the validity and practicality. The result showed thatthe module which had been developed based constructivism was valid and verypracticality according to the mathematicians and linguists.